Reply to treatment decisions and outcome in very elderly patients with diffuse large B‐cell lymphoma. Issue 20 (25th June 2015) - Williams, Jessica N.; Koff, Jean L.; Flowers, Christopher R.
<x xml:space="preserve">Abstract</x> Reduced doses of R‐CHOP, non‐anthracycline‐based regimens, and non‐pegylated liposomal doxorubicin are potential alternative regimens for elderly patients with diffuse large B‐cell lymphoma who cannot tolerate standard R‐CHOP. Radiation therapy with abbreviated R‐CHOP should also be further investigated as a treatment option in this population.